Syntheses of 1, 2, 4 Triazole Derivatives and their Biological Activity - Freddy H. Havaldar; Abhay R. Patil (E-Journal of Chemistry)
Cyclisation of [4-(4-oxo-2-phenyl-4H-quinazolin-3-yl)-phenoxy]-acetic acid-N'-(substituted phenyl)-thiosemicarbazides with sodium metal in 99.0 % ethanol gave 3-[4-(4-substituted phenyl-5-thioxo-4,5-dihydro-1H-1,2,4 triazol-3-ylmethoxy)- phenyl]-2-phenyl-3H-quinazolin-4-one . The structures of the newly synthesized compounds have confirmed by IR, 1H NMR and Mass spectra. The compounds have also been screened for their biological activity.